Graphical Web Based Tool for Generating Query from Star Schema - Anbar, Mohammad F.R. (2009)
Novice users have difficulty to generate structured query language from the star schemas because they are not familiar with formulating SQL queries and SQL syntax. This study proposed graphical web based tool to generate queries from star schema and represent the data in tabular or graphical forms which help novice user to formulate SQL query. A prototype for a web based tool to generate the query has been developed using Java Server Pages programming language. The developed tool can facilitate complex query construction which is faced by non-technical and/or novice users. The output of SQL query is presented in tabular and graphical forms which can help users especially top management in better understanding and interpreting query results.